Inhibitory effects of resistant maltodextrin on rat disaccharidases: Overestimation by the method measuring released glucose - Yugo Nakamura; Kayo Yamamoto; Yuko Uehara; Kouhei Nagai; Kunihiro Kishida (Journal of Functional Foods, 2023)
Resistant maltodextrin (RMD) attenuates the blood glucose response in healthy adults, as supported by meta-analysis. One of the potential mechanisms is disaccharidase inhibition. We hypothesized that the conventional method determining released glucose might lead to misestimation of the inhibitory effects because RMD is partly digested and the glucose amount released from RMD could change in the presence or absence of substrates. We examined digestibility change of RMD and compared the inhibitory effects by determination of released glucose (Glu method), fructose (Fru method), and p-nitrophenol from p-nitrophenyl- α -D-glucopyranoside (pNPG method). The Glu method overestimated the inhibition rate (18.9 to 60.2% for maltase). The Fru method showed inhibition for sucrase by 6.46 to 10.9% and isomaltase by 14.4 to 28.6%. The pNPG method showed α-glucosidase inhibition of 11.0 to 28.1%. These results indicate that the Glu method is not suitable for inhibition assay of partially digestible dextrin and that RMD has disaccharidase inhibition.